OPTIMASI DEASETILASI KHITIN DARI KULIT UDANG DAN CANGKANG KEPITING LIMBAH RESTORAN SEAFOOD MENJADI KHITOSAN MELALUI VARIASI KONSENTRASI NaOH - Puspawati, N. M.; Simpen, I N. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010)
Chitin resulted from treatment of shrimp and crab shells wasted of seafood restaurant, can be transformed into chitosan through deacetylation process using concentrated NaOH. This research aims to investigate the optimum condition of the deacetylation process to achieve a high yield and deacetylation degree of chitosan by varying the concentration of NaOH while temperature and length of reaction are made constant at 120oC for 4 hours. The concentration of NaOH used in this research was 50; 55; and 60%, respectively. All chitosan obtained were purified and characterized by FTIR. The deacetylation degree of chitosan was calculated based on FTIR spectra data. The result found, the optimum condition for deacetylation of chitin from shrimp shells at 120oC for 4 hours, was achieved using NaOH 60%, giving a high yield of 54.90% and deacetylation degree of 88.04%.. Using the same condition as for deacetylation chitin from shrimp, chitosan obtained from crab shells gave a better yield which was 62.76 %, and the deacetylation degree of 88.53%. Both chitosans obtained from shrimp and crab shells solubled in a 2% acetic acid solution.
Keywords: deacetylation, shrimp shells, crab shells, chitin, chitosan